EFEKTIFITAS KINERJA DEWAN KEHORMATAN WILAYAH DALAM MEMBINA DAN MENGAWASI NOTARIS (Studi pada Dewan Kehormatan Ikatan Notaris Indonesia Wilayah Jawa Timur) - Sugianto Sugianto (Widya Yuridika, 2019)
There are some forms of violation of the notary profession handled by the Regiona/ Honorary House one of which is the public notary functioning as "asongan" public notary, offering their services to banks. This violation happens because it is the public notary himself who is not fully able to obey its code. This condition is worsen because the public tbanksj that do not know that what the public notary has done ts to break the code. Moreover, there is another factor that it the Honorary House itself which is under performed according to some respondents. The Honorary House is facing some hindrances namely the feeling of "ewuh pakewuh" (being shy and reluctant) because this house should do something bad to its colleagues. Therefore, it is necessary to have some socializations to the people on the extstence of this House, so that the people as the users of the public notary will feel to be protected, the Honorary House should be more activated, so it will be able help the Notary Supervisory Agency do itsj ob. Then it is necessary to give enough fund to the Honorary House.